Flexible and Independent Control of Asymmetric Vortex Beams Based on Spin Multiplexing all Dielectric Metasurface - Wang, Qingyu; Li, Chenxia; Fang, Bo; Ke, Lan; Lu, Jianxun; Ma, Xiaoli; Hong, Zhi; Jing, Xufeng (Journal of lightwave technology, 2023)
Vortex beams carrying orbital angular momentum have important applications in optical communication, particle manipulation and quantum information. Vortex beams have multiplexed communication capabilities. Here, at the terahertz band, we propose a spin-multiplexed all-dielectric metasurface that combines vortex phase and encoding sequences. The metasurface can generate asymmetric vortex light with different topological charges under the condition of orthogonal circularly polarized light. Moreover, the flexible manipulation of the deflection angle of the vortex beam can be realized by changing the coding sequence. Meanwhile, the superposition of multifunctional coding sequences can also generate vortex beams with different states. Additionally, the focusing properties of the spin-multiplexed deflected vortex beam were analyzed. This work provides a new method for micro-nano integrated optics to generate deflected vortex light, which can be applied in data communication, micro-manipulation and other fields.